2016
DOI: 10.3892/mmr.2016.5272
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and bioinformatic analyses of spinal cord injury-induced skeletal muscle atrophy in rats

Abstract: Spinal cord injury (SCI) may result in skeletal muscle atrophy. Identifying diagnostic biomarkers and effective targets for treatment is an important challenge in clinical work. The aim of the present study is to elucidate potential biomarkers and therapeutic targets for SCI-induced muscle atrophy (SIMA) using proteomic and bioinformatic analyses. The protein samples from rat soleus muscle were collected at different time points following SCI injury and separated by two-dimensional gel electrophoresis and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…Importantly, myopenia occurring after SCI is associated with both substantial loss of sub-lesional muscle mass [ 13 , 16 ] and fatty infiltration of muscle [ 16 , 111 ], which together contribute to an obese somatotype [ 112 ], reduced whole-body metabolism [ 113 , 114 ], and increased risk for cardiometabolic disease. [ 112 ] Previous rodent studies of SCI contusion and transection have confirmed changes in sub-lesional muscle size and phenotype, [ 43 , 115 117 ] however, these changes have not been evaluated with respect to accompanying consequences. Beyond its notable trophic effects on skeletal muscle, UA reportedly promotes positive outcomes in models of diabetes and hyperlipidemia [ 118 , 119 ], making it an attractive treatment strategy for attenuating secondary health complications associated with cardiometabolic disorders in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, myopenia occurring after SCI is associated with both substantial loss of sub-lesional muscle mass [ 13 , 16 ] and fatty infiltration of muscle [ 16 , 111 ], which together contribute to an obese somatotype [ 112 ], reduced whole-body metabolism [ 113 , 114 ], and increased risk for cardiometabolic disease. [ 112 ] Previous rodent studies of SCI contusion and transection have confirmed changes in sub-lesional muscle size and phenotype, [ 43 , 115 117 ] however, these changes have not been evaluated with respect to accompanying consequences. Beyond its notable trophic effects on skeletal muscle, UA reportedly promotes positive outcomes in models of diabetes and hyperlipidemia [ 118 , 119 ], making it an attractive treatment strategy for attenuating secondary health complications associated with cardiometabolic disorders in SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on muscle atrophy have focused on animal models of disuse atrophy and denervation atrophy; muscle atrophy after SCI is usually classified as either one or a combination of these muscle atrophy models. However, the pathogenesis of muscle atrophy after SCI involves multiple factors, including signal transduction, immunity, electrical conduction, stimulation, and metabolism 20 , 21 . This complex situation cannot be attributed to a single molecular mechanism or simple combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Functional recovery of the animals was evaluated using the Basso Beattie Bresnahan (BBB) locomotor rating scale (17). The BBB was observed by two groups, and the observers were blinded to the design of current experiment (18). The BBB scores of rats were recorded prior to contusion operation and at 1, 3, 5, 7 and 14 days post-injury (dpi).…”
Section: Methodsmentioning
confidence: 99%